An investigation into the prehospital diagnosis, patient characteristics and treatment of cardiogenic acute pulmonary oedema (APO) patients: A scoping review - Lackay, Ruth (Division of General Surgery, 2024)
Introduction A scoping review was conducted to identify current clinical practice guidelines for the diagnosis and treatment of Cardiogenic Acute Pulmonary Oedema (CAPO) in the prehospital setting and to also discuss the application and relevance of these findings to low to middleincome countries (LMICs). Specific practice guideline elements that were reviewed included clinical presentation, timely diagnosis, triage, recommended treatment, and clinical referral pathway. Methods Published literature was systematically searched using the framework developed by Arksey and O'Malley. Using a priori-developed search strategy, electronic searches were performed in PubMed, Africa Wide, Scopus, Medline, and CINHAL databases to identify articles published in English between 2010 and 2022 relevant to Cardiogenic Acute Pulmonary Oedema (CAPO) in the prehospital setting. Two authors independently assessed whether each article met one or more of the five inclusion criteria, with disagreements resolved through either discussion or adjudication of a senior reviewer. A summary of the main themes contained within all eligible articles was developed using descriptive analysis. Results A total of 1193 articles were identified. In the screening process, 13 duplicate articles were removed and 1061 articles were removed based on title and abstract review. During full text review to determine eligibility, 84 articles were removed after review. A total of 35 articles meeting the inclusion criteria were included for final review and analysis. The following three themes were identified during the analysis: Clinical presentation of AHF and risk stratification, prehospital management and care according to best practice recommendations, and clinical referral and transportation pathways. Conclusion: The review highlighted key information on risk-stratifying CAPO patients to guide patientcentered care and transportation decision-making. Interestingly most of the published literature discovered in this scoping review were those published from high-income country settings, this reflects the gap in evidence on best practice recommendations that are contextfit for LMICS.